Madrasah From A Historical Perspective: Its Contribution to The Development of Islamic Education in Indonesia - Erwin Saputra; Fatiyah Auli Armedy; Idrus L (International Journal of Applied Research and Innovation, 2026)
This study examines the historical development of madrasah and its contribution to the evolution of Islamic education in Indonesia, addressing the persistent tension between traditional religious instruction and modern educational demands. Despite extensive scholarship, existing studies often lack critical synthesis regarding institutional transformation and epistemological adaptation. This research employs a non-empirical qualitative design based on historical and literature analysis, drawing upon scholarly articles, policy documents, and academic works to construct a comprehensive analytical framework. Data were systematically selected, categorized, and interpreted using a critical-historical approach to identify patterns of institutional change and conceptual shifts. The findings reveal that madrasah have evolved through phases of informal religious instruction, institutional formalization, and modern integration, reflecting adaptive responses to socio-political and educational pressures. Curricular transformation demonstrates a hybrid epistemology that integrates religious and general knowledge, enhancing the relevance of madrasah in contemporary contexts. Additionally, madrasah play a significant socio-educational role in expanding access to education and fostering social mobility, although challenges related to quality disparities and global pressures persist. The study concludes that madrasah remain pivotal in shaping Islamic education through a dynamic balance between tradition and innovation.